Green sustainable process for chemical and environmental engineering and science : biosurfactants for the bioremediation of polluted environments - Inamuddin, 1980-; Adetunji, Charles Oluwaseun (Elsevier, 2021)
Green Sustainable Process for Chemical and Environmental Engineering and Science: Biosurfactants for the Bioremediation of Polluted Environments explores the use of biosurfactants in remediation initiatives, reviewing knowledge surrounding the creation and application of biosurfactants for addressing issues related to the release of toxic substances in ecosystems. Sections cover their production, assessment and optimization for bioremediation, varied pollutant degradation applications, and a range of contaminants and ecological sites. As awareness and efforts to develop greener products and processes continues to grow, biosurfactants are garnering more attention for the potential roles they can play in reducing the use and production of more toxic products. Drawing on the knowledge of its expert team of global contributors, this book provides useful insights for all those currently or potentially interested in developing or applying biosurfactants in their own work.
Keywords: Biosurfactants.; Bioremediation.; Sustainable engineering.; elektronické knihy; electronic books